2015
DOI: 10.1371/journal.pone.0143367
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Gelatinase Associated Lipocalin (NGAL) in Leptospirosis Acute Kidney Injury: A Multicenter Study in Thailand

Abstract: AKI is one of the most serious complications of leptospirosis, an important zoonosis in the tropics. Recently, NGAL, one of the novel AKI biomarkers, is extensively studied in various specific settings such as sepsis, cardiac surgery, and radiocontrast nephropathy. In this multicenter study, we aimed to study the role of NGAL as an early marker and an outcome predictor of leptospirosis associated AKI. Patients who presented with clinical suspiciousness of leptospirosis were prospectively enrolled in 9 centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 23 publications
2
38
0
1
Order By: Relevance
“…However, it is not a specific biomarker for AKI vs sepsis [779; 782–790] and its origin in sepsis differs [791; 792]. Of course it can be the sepsis that leads to the AKI [793; 794]. Fairly obviously, while it does tend to be increased during PE, we again see its direct role as an antimicrobial and marker of sepsis as highly supportive of our present thesis.…”
Section: Proteomic and Similar Biomarkers-circulating And Placentalsupporting
confidence: 59%
“…However, it is not a specific biomarker for AKI vs sepsis [779; 782–790] and its origin in sepsis differs [791; 792]. Of course it can be the sepsis that leads to the AKI [793; 794]. Fairly obviously, while it does tend to be increased during PE, we again see its direct role as an antimicrobial and marker of sepsis as highly supportive of our present thesis.…”
Section: Proteomic and Similar Biomarkers-circulating And Placentalsupporting
confidence: 59%
“…The uDA1/Cr level was correlated with the level of uNGAL/Cr, which is a 25 kDa member of the lipocalin protein family that was first identified in activated human neutrophils [18], and also with the levels of uNAG/Cr, a lysosomal enzyme abundant in proximal kidney tubule cells. An increase of uNAG levels and tubular dysfunction in leptospirosis patients was reported previously [19], and serum and urine NGAL has been shown to be associated with acute kidney failure [12,20]. However, it has also been reported that urinary tract infections such as cystitis are also associated with uNGAL levels in the absence of AKI, as neutrophils secrete NGAL [21,22].…”
Section: Discussionmentioning
confidence: 78%
“…Azithromycin and doxycycline have been reported to be effective in the treatment of this disease [9]. Azithromycin was also shown to inhibit neutrophil activation [10,11], and involvement of neutrophils and elevation of neutrophil-related activation markers such as neutrophil gelatinase-associated lipocalin (NGAL) have been reported in leptospirosis patients [12]. We recently demonstrated that urinary leptospiral DNA, some of which is presumably from phagocytized bacteria in leukocytes, increased the detection rate of leptospirosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not a specific biomarker for AKI vs. sepsis (839, 842850) and its origin in sepsis differs (851, 852). Of course, it can be the sepsis that leads to the AKI (853, 854). Fairly obviously, while it does tend to be increased during PE, we again see its direct role as an antimicrobial and marker of sepsis as highly supportive of our present thesis.…”
Section: Proteomic and Similar Biomarkers – Circulating And Placentalmentioning
confidence: 99%